2022
DOI: 10.1177/09544119221085795
|View full text |Cite
|
Sign up to set email alerts
|

Workflow assessing the effect of Achilles tendon rupture on gait function and metatarsal stress: Combined musculoskeletal modeling and finite element analysis

Abstract: Achilles tendon rupture (ATR) incidence has increased among badminton players in recent years. The foot internal stress was hard to obtain through experimental testing. The purpose of the current research is to develop a methodology that could improve the finite element model derived foot internal stress prediction for ATR clinical and rehabilitation applications. A subject-specific musculoskeletal model was combined with a 3D finite element model to predict the metatarsal stress. The 80% point during the push… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The following deficiencies could be detectable from the present scrutiny: only data from two aerial strikes were selected for analysis, and no data analysis was conducted for the initiation and ending phases, mainly because the distance and amplitude of the subject's strikes were affected to some extent by the force measuring table and the experimental dummy. Meanwhile, the potential impact of various states (such as non-dominant and dominant legs) on sports injuries can be further analyzed; for this purpose, musculoskeletal finite element modeling can be employed to analyze the stress and strain effects on the human body, revealing potential sports injury situations [ [58] , [59] , [60] ].…”
Section: Discussionmentioning
confidence: 99%
“…The following deficiencies could be detectable from the present scrutiny: only data from two aerial strikes were selected for analysis, and no data analysis was conducted for the initiation and ending phases, mainly because the distance and amplitude of the subject's strikes were affected to some extent by the force measuring table and the experimental dummy. Meanwhile, the potential impact of various states (such as non-dominant and dominant legs) on sports injuries can be further analyzed; for this purpose, musculoskeletal finite element modeling can be employed to analyze the stress and strain effects on the human body, revealing potential sports injury situations [ [58] , [59] , [60] ].…”
Section: Discussionmentioning
confidence: 99%
“…According to research findings, ATR has been shown to result in reduced posterior muscle strength and tendon length [ 10 , 12 , 13 , 17 , 19 , 26 , 27 ], which, in turn, may lead to a decrease in plantarflexion range and an increase in dorsiflexion range [ [14] , [15] , [16] , 28 ]. Consequently, the individual's jumping ability may be negatively affected [ 24 , 25 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the limited feasibility of directly measuring tibiofemoral forces, a commonly employed approach is to combine medical imaging, musculoskeletal modelling [ 41 , 42 ], and finite elements analysis [ 28 , 43 ]. However, relatively few studies have examined tibiofemoral forces during countermovement jump (CMJ) in patients with ATR [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, advanced technologies are becoming increasingly common as rehabilitation therapeutic tools in the healthcare setting [1][2][3][4][5][6]. Among them is virtual reality (VR), which immerses the users into the artificial environment created by the computer simulation [7,8].…”
Section: Introductionmentioning
confidence: 99%